Pola peresepan obat antidiabetes pada pasien rawat jalan - Primadiamanti, Annisa; Malinda, Yun; Saputri, Gusti Ayu Rai (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2024)
Background: WHO (World Health Organization) predicts an increase in the number of people with diabetes mellitus in Indonesia in 2000, namely from 8.4 million to 21.3 million in 2030. Early combination therapy will achieve good glucose control and improve prognosis, especially microvascular complications. Purpose: To determine the pattern of diabetes medication prescribing for outpatients at A. Dadi Tjokrodipo General Hospital Bandar Lampung for the period January 2020 - December 2021. Method: A descriptive observational and retrospective using medical record data of hypertensive patients selected based on purposive sampling. Results: Showed that the patient characteristics were found to be mostly women 72%, aged 51-60 years 39%, drug characteristics, namely the biguanide drug class 36.1%, with OAD therapy 81%. The use of diabetes drugs in outpatients at A. Dadi Tjokrodipo Hospital Bandar Lampung for the period January 2020 – December 2021 is that the main drug of choice is the biguanide group with a percentage of 36.1%. The use of single OAD was 81%, the combination of OAD + long-acting insulin was 19%. Conclusion: The biguanide class of drugs is the first line for selecting long-acting insulin. Keywords: Antidiabetic; Diabetic; Prescribing Drugs. Pendahuluan: WHO (World Health Organization) memprediksikan kenaikan jumlah penyandang diabetes melitus di Indonesia pada tahun 2000 yaitu sebanyak 8,4 juta menjadi 21,3 juta pada tahun 2030. Terapi kombinasi dini akan mendapatkan kontrol glukosa yang baik dan memperbaiki prognostik terutama komplikasi mikrovaskuler. Tujuan: Untuk mengetahui pola peresepan obat diabetes pasien rawat jalan di RSUD A. Dadi Tjokrodipo Bandar Lampung periode Januari 2020 – Desember 2021. Metode: Observasional deskriptif dengan retrospektif menggunakan data rekam medik pasien diabetes yang dipilih berdasarkan purposive sampling. Hasil: Menunjukan pada karakteristik pasien didapatkan paling banyak perempuan 72% dengan usia 51-60 tahun 39%, karakteristik obat yaitu golongan obat biguanide 36,1% dengan terapi OAD 81%. Penggunaan obat diabetes pada pasien rawat jalan di RSUD A. Dadi Tjokrodipo Bandar Lampung periode Januari 2020 - Desember 2021 merupakan obat pilihan utama adalah golongan biguanid dengan presentase 36,1 %. Penggunaan OAD tunggal 81 %, kombinasi OAD +insulin long-acting 19%. Simpulan: Golongan obat biguanid menjadi lini pertama untuk pemilihan insuling long-acting.